2000
DOI: 10.1016/s0960-9822(00)00622-9
|View full text |Cite
|
Sign up to set email alerts
|

The Scabrous protein can act as an extracellular antagonist of Notch signaling in the Drosophila wing

Abstract: Notch (N) is a receptor for signals that inhibit neural precursor specification [1-6]. As N and its ligand Delta (DI) are expressed homogeneously, other molecules may be differentially expressed or active to permit neural precursor cells to arise intermingled with nonneural cells [7,8]. During Drosophila wing development, the glycosyltransferase encoded by the gene fringe (fng) promotes N signaling in response to DI, but inhibits N signaling in response to Serrate (Ser), which encodes a ligand that is structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
28
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 27 publications
5
28
0
Order By: Relevance
“…and N.E.B., unpublished). Because the same UAS-Dl transgenes did activate N during wing development, leading to formation of ectopic wing margin (Lee et al, 2000), did activate N when expressed anterior to the morphogenetic furrow, leading to accelerated furrow Y. Li and others † The total includes R4 cells in chirally reversed ommatidia that were otherwise constructed normally.…”
Section: Does Not Activate N In R8 Precursor Cellsmentioning
confidence: 99%
“…and N.E.B., unpublished). Because the same UAS-Dl transgenes did activate N during wing development, leading to formation of ectopic wing margin (Lee et al, 2000), did activate N when expressed anterior to the morphogenetic furrow, leading to accelerated furrow Y. Li and others † The total includes R4 cells in chirally reversed ommatidia that were otherwise constructed normally.…”
Section: Does Not Activate N In R8 Precursor Cellsmentioning
confidence: 99%
“…To investigate this, we turned to ectopic expression experiments. Ectopic Sca expression can inhibit N signaling in the wing margin (Lee et al, 2000). UAS-gp150 transgenic flies were prepared and the dppGal4 transgene used to drive gp150 expression in a stripe across the wing, as described previously for Sca.…”
Section: Gp150 Is Required For Sca Activitiesmentioning
confidence: 99%
“…Sca protein appears to prevent Dl from activating of N in this ectopic expression assay. The results strongly suggest that Sca protein targets N signaling, although not defining the exact role of Sca in normal development (Lee et al, 2000). In other experiments, Powell et al (Powell et al, 2001) reported that when ectopically expressed in pupal retina, Sca protein was preferentially stabilized in cells expressing N and that such stability depended on EGF repeats 19-26 of the N extracellular domain.…”
Section: Introductionmentioning
confidence: 95%
“…Ato also activates signals that repress ato expression in nearby cells and contribute to lateral inhibition. These include the ligand Delta (Dl) for the Notch (N) receptor, the secreted factor Scabrous (Sca), which can diffuse at least a few cell diameters and affects Notch signaling (12)(13)(14)(15)(16), and signals that interfere with Hh signaling posterior to the MF (3,4,17,18). Notch signaling plays an additional role in ato induction, in combination with the nonautonomous signal Decapentaplegic (Dpp) (19,20).…”
mentioning
confidence: 99%